Impact of the Ottawa model on opiate screening and smoking cessation in methadone-treated patients with opioid use disorder: A retrospective cohort analysis - Shu-Wua Lee; Po-Chung Yu; Ting-Ting Yen; Chiann-Yi Hsu; Li-Jou Lai; I-Chun Chen; Ting-Gang Chang (Tobacco Induced Diseases)
Introduction Approximately 60 million individuals worldwide used opioids in 2021, constituting 1.2% of the global adult population. This study aimed to evaluate the effectiveness of integrated treatment strategies for opioid use disorder and nicotine use disorder by assessing the impact of smoking cessation within a methadone treatment framework.